The N400 Effect during Speaker-Switch—Towards a Conversational Approach of Measuring Neural Correlates of Language - Goregliad Fjaellingsdal, Tatiana; Ruigendijk, Esther; Scherbaum, Stefan; Bleichner, Martin G. (Frontiers in Psychology, 2016)
Language occurs naturally in conversations. However, the study of the neural underpinnings of language has mainly taken place in single individuals using controlled language material. The interactive elements of a conversation (e.g., turn-taking) are often not part of neurolinguistic setups. The prime reason is the difficulty to combine open unrestricted conversations with the requirements of neuroimaging. It is necessary to find a trade-off between the naturalness of a conversation and the restrictions imposed by neuroscientific methods to allow for ecologically more valid studies. Here we make an attempt to study the effects of a conversational element, namely turn-taking, on linguistic neural correlates, specifically the N400 effect. We focus on the physiological aspect of turn-taking, the speaker-switch, and its effect on the detectability of the N400 effect. The N400 event-related potential reflects expectation violations in a semantic context; the N400 effect describes the difference of the N400 amplitude between semantically expected and unexpected items. Sentences with semantically congruent and incongruent final words were presented in two turn-taking modes: (1) reading aloud first part of the sentence and listening to speaker-switch for the final word, and (2) listening to first part of the sentence and speaker-switch for the final word. A significant N400 effect was found for both turn-taking modes, which was not influenced by the mode itself. However, the mode significantly affected the P200, which was increased for the reading aloud mode compared to the listening mode. Our results show that an N400 effect can be detected during a speaker-switch. Speech articulation (reading aloud) before the analyzed sentence fragment did also not impede the N400 effect detection for the final word. The speaker-switch, however, seems to influence earlier components of the electroencephalogram, related to processing of salient stimuli. We conclude that the N400 can effectively be used to study neural correlates of language in conversational approaches including speaker-switches.